In vitro cytotoxicity analysis of sulfated polysaccharides from green seaweed Codium tomentosum Stackhouse, 1797 - Pagolu Navya, Samantha Sekar Khora (Journal of Applied Pharmaceutical Science, 2017)
Algae polysaccharides are commonly used in alternative medicine. Toxicity study of the isolated polysaccharide was carried out prior to the exploration of its bioactivities. In the present study we examined the toxicity of sulfated polysaccharides isolated from marine green algae Codium tomentosum. In this in vitro study, normal mouse fibroblast cells (L929) cells were used and Cytotoxicity was screened using 3-(4, 5-d imethylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide (MTT) reduction assay. This study showed that Polysaccharides from Codium tomentosum had no toxic effects, so these polysaccharides can be utilized for future studies.
Keywords: Codium tomentosum, Polysaccharides, Toxicity, L929 cells, MTT assay.